Baby Weight And Length Based On Arduino Uno With Combination Of Ultrasonic Sensor Hc-Sr04 And Weight Sensor (Load Cell) - Sujiwa, Akbar; Marta, Bayu Tirta; Afif Nuril Musthofa (BEST, 2024)
Infant development and growth at the age of 0 to 1 year. Babies are easily affected by malnutrition or, if parents ignore the development and growth of the baby. Generally, parents will take their babies to Posyandu or Midwives to have their weight weighed and the length of the baby's body measured. At the time of measuring the baby's body weight and length still using separate and manual measurements. Therefore we need a weighing device that is able to measure the baby's weight and baby's length simultaneously. Then an "Arduino Uno-Based Baby Weight and Length Weighing Device was made by Combining the HC-SR04 Ultrasonic Sensor and the Weight Sensor (Load Cell)" to simplify the process of measuring the baby's weight and length simultaneously and recording the results of these measurements. The benefit of making this tool is that it helps parents to know the growth and development of their babies aged 0 to 1 year. And the purpose of making this tool is to measure the baby's weight and length simultaneously, which in general the process of measuring the baby's weight and length is still not automatic, and still uses analog or digital scales but there is no tool that can measure automatically and simultaneously in the process of measuring the baby's weight and length. From here we submit a research proposal in which the results of this research proposal are expected to contribute well as a first step in our research so that in the process of designing the tool it can work well and be useful for parents and medical personnel